Openness to Concerns of Host Country Population Improves Attitudes Towards Immigrants - Tobias Stöhr; Philipp C. Wichardt (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper reports results from a randomized questionnaire study among German citizens regarding their attitudes towards Syrian refugees. Being shown a picture of an alleged Syrian refugee the description of whom was varied, respondents were asked to indicate their attitude towards that person in various domains on a 6-point Likert-scale. Among other things, the data show that people who are more risk averse are also less sympathetic, empathic, trusting. However, once the refugee is described as being open towards concerns in the German population – regarding cultural change, arising costs and increasing violence – reported levels of liking and trust increase substantially, especially for risk averse people. Moreover, we find that having close non-German friends or relatives increases the willingness to interact with immigrants. Thus, the data emphasize two aspects: (1) the importance of being open for the concerns of the local population for them to be open minded, i.e.~sympathetic and trusting, and (2) the relevance of personal experience for the willingness to interact. Finally, we find that overall women are more empathic but less trusting and more hesitant regarding actual interaction.
Keywords: F22; Z10; Z12; 330